2016
DOI: 10.1186/s12876-016-0499-z
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene receptor expression in esophageal squamous cell cancer and non-transformed esophageal epithelium: a matched case control study

Abstract: BackgroundLeukotriene B4 (LTB4R and LTB4R2) and cysteinyl leukotriene receptors (CYSLTR1 and CYSLTR2) contribute to malignant cell transformation. We aimed to investigate the expression of LTB4R, LTB4R2, CYSLTR1 and CYSLTR2 in esophageal squamous cell carcinoma and adjacent non-transformed squamous epithelium of the esophagus, as well as in control biopsy samples from esophageal squamous epithelium of patients with functional dyspepsia.MethodsExpression of LTB4R, LTB4R2, CYSLTR1 and CYSLTR2 was analyzed by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In recent years, a number of studies have indicated the important role of LOX-derived leukotrienes in carcinogenesis and cancer progression [ 6 , 20 , 26 ]. The tumor-promoting role of the LTB 4 pathway has been recognized in many cancers, such as prostatic cancer [ 27 ], esophageal cancer [ 28 ], head and neck cancer [ 29 ], gastric cancer [ 30 ], and colon cancer [ 31 ]. Cysteinyl leukotrienes (LT), including LTC 4 , LTD 4 , and LTE 4 , which are originally recognized for their effects in promoting bronchoconstriction, inflammation, mucus secretion, and microvascular permeability, have also been gradually understood for their contribution in carcinogenesis and cancer progression [ 4 , 6 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of studies have indicated the important role of LOX-derived leukotrienes in carcinogenesis and cancer progression [ 6 , 20 , 26 ]. The tumor-promoting role of the LTB 4 pathway has been recognized in many cancers, such as prostatic cancer [ 27 ], esophageal cancer [ 28 ], head and neck cancer [ 29 ], gastric cancer [ 30 ], and colon cancer [ 31 ]. Cysteinyl leukotrienes (LT), including LTC 4 , LTD 4 , and LTE 4 , which are originally recognized for their effects in promoting bronchoconstriction, inflammation, mucus secretion, and microvascular permeability, have also been gradually understood for their contribution in carcinogenesis and cancer progression [ 4 , 6 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced GJA1 expression was associated with high levels of preoperative PSA, high Gleason score, and advanced pT stage and was an independent predictor for shortened postoperative BCR-free survival [ 37 ]. Forced expression of GJA1 induced apoptosis of PCa cells by downregulation of Bcl-2 expression and upregulation of caspase-3 activity [ 38 ]. By immunohistochemistry (IHC) and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) analyses, Venerito et al found CYSLTR1 expression was decreased by 0.26-fold in esophageal squamous cell cancer tissues compared to control mucosa [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A significant upregulation of testican‐1 (SPOCK1) in OSCC patients compared to healthy control (HC) implied that SPOCK1 could serve as an early biomarker as well as prognostic marker due to tobacco use . Significant intracellular proteins for the early detection of ESCC include the proteasome activator subunit 2 β (PA28β) protein, leukotriene B4 receptor (LTB4R) protein, cysteinyl leukotriene receptor 2 (CYSLTR2) protein, and glutathione S‐transferase omega 1 (GSTO1) protein . PA28β and CYSLTR2 are downregulated; whereas, LTB4R and GSTO1 are upregulated in the ESCC tissues.…”
Section: Biomarkers In Oscc and Esccmentioning
confidence: 99%